Stereoselective synthesis of whisky lactone isomers catalyzed by bacteria in the genus Rhodococcus - Hernik, Dawid; Gatti, Francesco; Brenna, Elisabetta; Szczepańska, Ewa; Olejniczak, Teresa; Boratyński, Filip (Frontiers in Microbiology, 2023)
Whisky lactone is a naturally occurring fragrance compound in oak wood and is widely used as a sensory additive in food products. However, safe and efficient methods for the production of its individual enantiomers for applications in the food industry are lacking. The aim of this study was to develop an efficient and highly stereoselective process for the synthesis of individual enantiomeric forms of whisky lactones. The proposed three-step method involves 1) column chromatography separation of a diastereoisomeric mixture of whisky lactone, 2) chemical reduction of cis- and trans-whisky lactones to corresponding syn- and anti-diols, and 3) microbial oxidation of racemic diols to individual enantiomers of whisky lactone. Among various bacteria in the genera Dietzia, Gordonia, Micrococcus, Rhodococcus, and Streptomyces, R. erythropolis DSM44534 and R. erythropolis PCM2150 effectively oxidized anti- and syn-3-methyl-octane-1,4-diols (1a-b) to corresponding enantiomerically pure cis- and trans-whisky lactones, indicating high alcohol dehydrogenase activity. Bio-oxidation catalyzed by whole cells of these strains yielded enantiomerically pure isomers of trans-(+)-(4S,5R) (2a), trans-(–)-(4R,5S) (2b), and cis-(+)-(4R,5R) (2d) whisky lactones. The optical density of bacterial cultures and the impact of the use of acetone powders as catalysts on the course of the reaction were also evaluated. Finally, the application of R. erythropolis DSM44534 in the form of an acetone powder generated the enantiomerically enriched cis-(–)-(4S,5S)-isomer (2c) from the corresponding syn-diol (1b). The newly developed method provides an improved approach for the synthesis of chiral whisky lactones.